Effect of Azithromycin on Asthma Remission in Adults With Persistent Uncontrolled Asthma - Dennis Thomas; Vanessa M. McDonald; Sean Stevens; Melissa Baraket; Sandra Hodge; Alan L. James; Christine Jenkins; Guy B. Marks; Matthew Peters; Paul N. Reynolds; John W. Upham; Ian A. Yang; et al. (2024)
Asthma remission is a potential treatment goal.